English-Speaking Anxiety among Preservice EFL Teachers during Teaching Practicum: A Quantitative Survey Study - Deni Asrida; Siska Febriyanti (FOSTER: Journal of English Language Teaching, 2026)
Speaking anxiety is widely recognised as one psychological obstacle to learning English as a Foreign Language (EFL). It has a substantial effect on pre-service teachers since they are expected to utilize English while they are learning how to teach. Although ample of research has examined speaking anxiety among EFL learners, empirical studies focusing on preservice EFL teachers during the teaching practicum phase remain limited particularly within Indonesian Islamic education teacher context. This research investigated the speaking anxiety of pre-service EFL teachers at UIN Mahmud Yunus Batusangkar who had completed their teaching practice. A quantitative survey design was employed, and data were collected using a speaking anxiety questionnaire. The data were analysed using descriptive statistic through SPSS version 26. The data findings revealed that the majority of participants experienced speaking anxiety (72.3%) were classified as moderate level of anxiety. Additionally, 13.9 % of participants fell into the high anxiety category while another 13.9% were categorized as having low anxiety. These results indicate that speaking anxiety is common and tangible experience although it generally remains manageable level. The findings suggest important pedagogical implications for EFL teacher education suggesting that the integration of positive teaching models, inclusive teaching simulations and helpful feedback may help reduce anxiety and help pre-service teachers to speak better. This study offers practical recommendation to strengthen preservice teachers in their language skills and better prepare them for classroom practice.